Exploring EFL Preservice Teachers’ Academic Integrity of Using ChatGPT in Educational Institutions - Made Wahyu Darmayasa; I Putu Indra Kusuma; Luh Indrayani (Universitas Pendidikan Ganesha, 2025)
This study aimed to explore the perceptions and strategies of EFL preservice teachers in using ChatGPT while maintaining academic integrity. Using a case study approach, the research investigated the experiences of sixth-semester students at a higher education institution in Buleleng, Bali, during the 2024/2025 academic year. Data were collected through semi-structured interviews and analyzed using thematic analysis. The results revealed one main theme and three subthemes: (1) ChatGPT as a brainstorming tool, not a final product; (2) Paraphrasing and cross-checking as ethical practices; and (3) Awareness of the risks of overreliance. The findings indicated that participants possessed ethical awareness in using ChatGPT strategically and responsibly. In addition, they demonstrated a tendency to avoid excessive reliance on technology and showed greater confidence in their own abilities. This study contributed to a deeper understanding of ethical AI use in higher education settings.